STRATEGI KOMUNIKASI PEMASARAN YAYASAN RUMAH QUR’AN VIOLET DALAM MENINGKATKAN MINAT MASYARAKAT DI KOTA PINANG KABUPATEN LABUHANBATU SELATAN - Ricky Ricky; Suheri Harahap; Anang Anas Azhar (Bajang Institute, 2023)
This study aims to find out how the marketing communication strategy used by the Rumah Quran Violet Foundation in attracting public interest as individuals engaged in Islamic religious education, the second is to find out what obstacles are experienced in carrying out the promotion process. This study uses a descriptive qualitative research method. There were three informants in this study, namely the Head of the Foundation Management, Teachers who teach at the Foundation, and the surrounding community. Data collection techniques are in-depth interviews, observation, and literature study. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that the Rumah Quran Foundation uses a publication strategy and conducts seminars, brochures and social media to increase public interest. With the existence of print media and online media owned by the Foundation, it can publish all activities that have been, and are being carried out. The foundation's obstacles in attracting community interest, firstly, is convincing their children to study at the Rumah Quran Violet Foundation and secondly, intense competition between Quran educational institutions.